2020
DOI: 10.1097/md.0000000000019759
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiac rehabilitation programs on left ventricular remodeling after acute myocardial infarction

Abstract: Introduction: While the role of early mobilization in the immediate postinfarction period has been well demonstrated, little is known in present about the link between early mobilization and reduction of systemic inflammation. At the same time, the impact of early mobilization on regression of left ventricular remodeling has not been elucidated so far.Material and methods: Here we present the study protocol of the REHAB trial, a clinical descriptive, prospective study, conducted in a single-center, with the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…In 2014, a study conducted in Slovenia found that patients with acute MI had higher baseline levels of hs-CRP than healthy individuals; while, after a 2-week CR was applied, hs-CRP significantly diminished in the non-smokers (P < 0.006), but not among the smoker patients [14]. A recent study in Romania showed that CR is as much effective as statins in reducing the hs-CRP levels among acute MI patients [15]. Munk et al reported that after 6 months of supervised high-intensity interval training programme in patients with stable angina, there was a reduction if CRP levels, which, in turn, was associated with a significant reduction of late luminal loss following PCI [16].In contrast, some studies did not find significant differences in inflammatory markers after CR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, a study conducted in Slovenia found that patients with acute MI had higher baseline levels of hs-CRP than healthy individuals; while, after a 2-week CR was applied, hs-CRP significantly diminished in the non-smokers (P < 0.006), but not among the smoker patients [14]. A recent study in Romania showed that CR is as much effective as statins in reducing the hs-CRP levels among acute MI patients [15]. Munk et al reported that after 6 months of supervised high-intensity interval training programme in patients with stable angina, there was a reduction if CRP levels, which, in turn, was associated with a significant reduction of late luminal loss following PCI [16].In contrast, some studies did not find significant differences in inflammatory markers after CR.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a study conducted in Slovenia found that patients with acute MI had higher baseline levels of hs-CRP than healthy individuals; while, after a 2-week CR was applied, hs-CRP significantly diminished in the non-smokers ( P < 0.006), but not among the smoker patients [14]. A recent study in Romania showed that CR is as much effective as statins in reducing the hs-CRP levels among acute MI patients [15]. Munk et al .…”
Section: Discussionmentioning
confidence: 99%
“…Especially for patients with AMI complicated by CS, primary percutaneous coronary intervention (PCI) should be strongly considered and may be life-saving. [2][3][4] In very young patients, AMI carries a significant morbidity, being associated with a strong psychological impact and financial burden for the patient and their family. 5 At the same time, in young patients suffering an AMI, CS is frequently associated, requiring a rapid diagnosis and supportive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Left ventricular dysfunction (LVD) is the most common cause of CS, being reported as the primary cause of CS in 74.5% of patients with acute heart failure. 2,10 In young patients aged <35 years, AMI is poorly characterized, although it is estimated to be less than 2%. Fur-thermore, its occurrence at a young age affects the productive age group, with a strong socioeconomic impact.…”
Section: Introductionmentioning
confidence: 99%